Frontotemporal Dementia - Perry, David C.; Miller, Bruce L. (Seminars in Neurology, 2013)
Frontotemporal dementia (FTD) encompasses several clinical syndromes that involve a progressive change in behavior and/or language; it is more common than Alzheimer's disease in early-onset dementia under the age of 60 years. In the behavioral variant of FTD (bvFTD) patients have social and emotional changes with prominent disinhibition, apathy, lack of empathy, changes in diet, and repetitive behaviors. Motor neuron disease or parkinsonism are seen in association with bvFTD. Frontal and/or temporal atrophy are often seen on structural brain imaging. Several pathological entities can cause bvFTD, and they are defined by the presence of specific abnormal protein accumulations. Most cases are characterized by accumulation of the proteins tau, TAR-DNA-binding protein-43 (TDP-43), and fused in sarcoma (FUS). Though most cases are sporadic, a variety of genes have been identified that cause autosomal dominant forms of FTD. The most common mutations occur in C9ORF72, MAPT, and GRN. No disease-modifying treatments have been currently identified, but limited evidence supports the use of antidepressants or neuroleptics in symptomatic management, and education regarding nonpharmacologic methods may be helpful to caregivers.
Keywords: frontotemporal dementia; motor neuron disease; Pick's disease; neurodegenerative disease